Legado da cultura alemã na literatura de Guimarães Rosa - Pereira Siqueira, Ivan Cláudio (2011)
João Guimarães Rosa was strongly influenced by the German literature, philosophy and music. The German tradition and its methods of associations suggested him to develop his own methodologies from the substrates provided by traditional Brazilian songs. This paper shows the general effects of musical techniques in short-stories of
http://creativecommons.org/licenses/by-nc/3.0/de/deed.de ; info:eu-repo/semantics/openAccess
Keywords: Rosa; João Guimarães; Wagner; Richard / Parsifal; Literatur; Musik; Heidegger; Martin